Integrated physiological, transcriptomic, and metabolomic analyses provide new insights into hypoxia tolerance in large yellow croaker (Larimichthys crocea) - Yibo Zhang; Jie Ding; Xuelei Wang; Ran Meng; Songpeng Jia; Xiongfei Wu; Junquan Zhu; XiaoMing Peng; Weiliang Shen (Marine Pollution Bulletin, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Groundwater dynamics induced by tunneling and reservoir filling at the site of Kala hydropower project - Ao Liu; Ying-Feng Zhang; Yi-Feng Chen; Ran Hu; Zhibing Yang; Jia-Qing Zhou; Hai-Sheng Zheng; Heng-Yi Gan; Bin Chen; En-Ming Zhang (Tunnelling and Underground Space Technology, 2026)

Complex enzymolysis-derived peanut peptides: in silico selection of antioxidant peptides, emulsion-microcapsule encapsulation, and in vitro digestive performance evaluation - Chengli Jia; Yansheng Wang; Tiantian Ran; Zhiqing Gong; Wenjia Cui; Shasha Song; Jian Zhang; Furong Hou; Junyan Shi; Fengjuan Jia; Wenliang Wang (Food Research International, 2026)

Gramineous Plants as Phytoremediation Candidates for Metal Contaminated Mining Soils under Drought Stress - Honglei Jia; Zhiwei Ran; Qing Wang; Haodong An; Ting Wei; Chunping Zhang; Gang Zhu; Junkang Guo (Water, Air, & Soil Pollution, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Making waves: Harnessing the disinfection byproduct chlorite as an oxidant precursor for micropollutant abatement - Xi Zhang; Yimeng Ma; Mingkai Jia; Wanxin Li; Jiarui Han; Rihui Li; Xin Yang; Ran Yin; Hongqiang Ren (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Fe-modified tea waste biochar enhances short-term soil organic carbon sequestration: Mechanisms and economic benefit - Weifeng Chen; Huiying Zhang; Yan Wang; Yun Xia; Pingping Lian; Hui Jia; Abdallah Abdelfattahe; Jinzhi Ni; Ran Wei (Environmental Research, 2026)

Peak greening at moderate shrinking intensity across Chinese counties - Ran Chen; Wenxiao Jia; Kai Wang; Xinyuan Zhang; Jiaxuan Xin; Wenjian Li; Zhijun Zhang; Junling He (Journal of Environmental Management, 2026)

Carbon and phosphorus regeneration during organic matter decomposition in aquatic ecosystems: characteristics, mechanisms, and environmental effects - Chao Yin; Yan Zeng; Jingan Chen; Peng Liao; Jia Yu; Guangrong Ran; Baohua Xiao; Xudong Guo; Ziyan Zhang; Jingfu Wang; Haiquan Yang; Quan Yuan (Geochimica et Cosmochimica Acta, 2026)

How chloride salts modulate the unfrozen water films and control interfacial strength in frozen porous media: A nanoscale perspective - Jiachuan Ran; Yuanming Lai; Mingyi Zhang; Xinyu Jia; Xulong Gao; Wansheng Pei; Jing Zhang; Tiantian You (Computers and Geotechnics, 2026)

Effects of salinity management practices on the soil organic carbon stock in China's salinized soils: A meta-analysis - Wenchao Zhang; Ran Li; Yangyang Sun; Zhentao Sun; Shujuan Wang; Jia Liu; Yan Li; Lizhen Xu; Yonggan Zhao (CATENA, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Spatiotemporal and process-refined assessment of full-chain GHG emissions and mitigation potential in China’s aluminum industry - Jia-Ran Zhang; Jia-Ning Kang; Bao-Jun Tang; Yu-Jie Hu (Resources, Conservation and Recycling, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Cerebral blood flow alterations in non-auditory tinnitus: implications for cerebral venous congestion pathophysiology - Lu Liu; Milan Jia; Hui Li; Yifan Zhou; Huimin Jiang; Weiyue Zhang; Chenxia Zhou; Jiangang Duan; Ran Meng; Chen Zhou; Xunming Ji (Brain Imaging and Behavior, 2026)

Urban vegetation resilience to compound drought–heat events: Resistance rises but recovery declines across 232 Chinese cities - Kai Wang; Wenxiao Jia; Ran Chen; Chengzhang Xia; Xianzhi Wang; Jian Chen; Yanlong Zhang (Agricultural and Forest Meteorology, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Molecular-scale insights into the freezing of surface-confined aqueous solutions on montmorillonite - Jiachuan Ran; Yuanming Lai; Xulong Gao; Jing Zhang; Ruiqiang Bai; Yanqiao Zhou; Kunyu Li; Pengchang Wei; Jiwei Jia (Computers and Geotechnics, 2026)

Distinct molecular complexing mechanisms of smoke dissolved organic matters (SDOMs) from various solid fuels combustion toward heavy metals: New insights based on FT-ICR-MS, two dimensional fluorescence EEM and FTIR - Yixin Xu; Shiming Xu; Yue Cheng; Weifeng Chen; Huiying Zhang; Hui Jia; Ran Wei; Jinzhi Ni (Fuel, 2026)

Insights into the binding mechanism of Monascus pigment with Holo-ovotransferrin by multispectral and molecular dynamics simulation - Yan Fan; Xi-Yuan Guan; Can-Huan Liang; Jia-Lin Chen; Si-Ran Zhang; Sheng Huang; Qin Wang; Wen-Hua Yang (Food Chemistry, 2026)

Water soluble polysaccharides from the fruits of Lycium barbarum L. improve glucose and lipid metabolism and boost immune function in elderly mice fed a high-fat diet - Wanyi Wang; Haiyu Shi; Meng Zhang; Jia Mi; Lu Lu; Bo Jin; Lutao Zhang; Abdul Rehman; Chunhong Liu; Yamei Yan; Linwu Ran (Food Bioscience, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Simultaneous control of organic chloramines and emerging contaminants in swimming pool water using far-UVC irradiation - Mingkai Jia; Yuliang Zhang; Xinyu Zhang; Wanxin Li; Ran Yin; Xinkun Ren (Water Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Responses of carbon monoxide photoproduction in surface seawater to environmental changes under simulated solar radiation - Xuan Ji; Ming-Liang Zhao; Yi-Ran Jia; Cai-Jie Zhang; Qi-Mei Du; Jing Zhang; Gui-Peng Yang (Marine Chemistry, 2026)

Far-UVC photolysis of chlorine dioxide for micropollutant abatement in water - Xinyu Zhang; Jing Zhao; Mingkai Jia; Chii Shang; Ran Yin; Hongqiang Ren (Journal of Hazardous Materials, 2026)

Synthesis of chitosan-phytic acid/TiO2 antioxidant composites for coal spontaneous combustion prevention - Yuanyuan Li; Xiaoling Xu; Ran Zhang; Xingbao Yang; Kun Jia (Fuel, 2026)

Sulfonated polyarylene ether nitrile membranes impregnated with silver nanoparticles for enhanced dye/salt separation - Qimeng Ran; Chenyi Xiong; Junni Xie; Libo Hao; Xingbao Yang; Xiaohong He; Dawei Zhang; Dongsheng Wang; Xiaobo Liu; Kun Jia (Chemical Engineering Journal, 2026)

Molecular-scale insights into the freeze-thaw process of aqueous and saline solutions in hydrated‑calcium-silicate gel pores - Jiachuan Ran; Yuanming Lai; Mingyi Zhang; Fan Yu; Te Liang; Wansheng Pei; Hongwei Li; Xulong Gao; Jiwei Jia (Cold Regions Science and Technology, 2026)

CD33 Isoform Splicing Dysregulation: A Molecular Determinant of Microglial Dysfunction in Alzheimer’s Disease Pathology - Xiao-Yan Li; Yu Zhang; Zhao Ran; Jia-Xin Luo; Xiao-Qin Yu; Mei-Hong Lu (Molecular Neurobiology, 2026)

HPLC-UV guided isolation of anti-inflammatory polyacetylene glucosides from Carthamus tinctorius L. - Yong-Xiang Wang; Jia-Xu Bao; Ran Wang; Xian Zhang; Yun-Fang Zhao; Peng-Fei Tu; Hui-Xia Huo; Jun Li (Phytochemistry, 2025)

Optimizing housefly larval bioconversion of silkworm excrement through wheat bran Supplementation: Enhanced cellulose degradation and nutrient recovery - Chen Chen; Yuanhao Zhang; Xueming Xu; Xueping Jiang; Jieling Zhou; Jia Kong; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

A HOF-COF hybrid photocatalyst for sacrificial agent-free uranium extraction via photogenerated-H2O2-mediated precipitation - Fei Han; Qiyue Zhang; Xia Wang; Wei Liu; Ran Jia; Xiaomei Wang; Zhongyue Li (Chemical Engineering Journal, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

Cyanobacterial dominance under CO2(aq)-limited conditions increases ecological risks in karst reservoirs - Guangrong Ran; Jingan Chen; Ziyan Zhang; Yan Zeng; Chao Yin; Jia Yu; Dong Wu; Haijun Yuan; Moshan Cen (Water Research, 2025)

PDA@SF@Nb hydrogel for a multifaceted bone defect therapy strategy via IL-6/IL-17/STAT3 signaling pathway - Zihua Li; Qinghua Tian; Rongfeng Zhang; Pei Wang; Limin Fan; Zhaoyang Ran; Lei Zhou; Zenghui Wu; Jia Tan; Weiming Guo; Yao Li (Chemical Engineering Journal, 2025)

Preparation, identification, and molecular mechanism of novel DPP-IV inhibitory peptides from pumpkin seed: In silico screening and experimental validation - Xiya Chen; Wenhao Zhang; Yuexin Pan; Jia Ran; Xia Liu; Xiaodong Yu; Qiyi He (Food Chemistry, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Feedback inhibition derived from hydrogen sulfide in microbial sulfidogenic process via elemental sulfur disproportionation - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xuchen Ba; Wenyan Mao; Wenke He; Cong Fang; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Genomic and transcriptomic insights into the cellulose-degrading mechanism of Bacillus subtilis DC-11 and its novel cellulose catabolic pathway - Chen Chen; Minqi Zhang; Yuanhao Zhang; Xueping Jiang; Jia Kong; Jieling Zhou; Gaiqun Huang; Ran Zhang; Hao Li; Zhongzheng Gui (Archives of Microbiology, 2025)

A novel ciprofloxacin-degrading bacteria Phytobacter diazotrophicus SMX isolated from silkworm faeces: characteristics, degradation metabolites, and toxicity assessment - Jia Kong; Xueping Jiang; Yuqi Li; Jielin Zhou; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Asia-Pacific Entomology, 2025)

Assessment of carbon sinks caused by the chemical weathering of carbonate rocks under the influence of exogenous acids: Methods, progress, and prospects - Luhua Wu; Xiaoyong Bai; Chaojun Li; Huiwen Li; Yue Cao; Chen Ran; Sirui Zhang; Lian Xiong; Chaochao Du; Guangjie Luo; Fei Chen; Heng Wei; et al. (Science China Earth Sciences, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Quantitatively tracing the decomposition of endogenous particulate organic carbon during sinking in (sub-)deep reservoirs: Using radiocarbon isotopes Δ14C - Chao Yin; Yan Zeng; Jingan Chen; Guangrong Ran; Haiquan Yang; Jia Yu; Jingfu Wang; Ziyan Zhang; Xudong Guo (Water Research, 2025)

Bed-immersion-ratio variation as an efficient strategy to regulate denitrification efficiency directionally in elemental sulfur packed-bed reactors - Guijiao Zhang; Hao-Ran Xu; Wenwei Liao; Jia-Min Xu; Na Zhang; Daheng Ren; Xinjie Chen; Wenyan Mao; Xiangli Zeng; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Effect of Bacillus velezensis T23 solid-state fermentation product on growth, gut and liver health, and gut microbiota of common carp (Cyprinus carpio) - Xingyu Chen; Shubin Liu; Tsegay Teame; Jia Luo; Yao Liu; Qingwen Zhou; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Zhen Zhang; Zhigang Zhou (Aquaculture, 2025)

Spatiotemporally tumor ferritin disruption enhances sorafenib induced ferroptosis in hepatocellular carcinoma - Bo Liu; Jie Cheng; Wenli Zhang; Ying Luo; Jia Liu; Sijin Chen; Qianying Du; Jie Xu; Lian Xu; Zhongsheng Xu; Yun Liu; Zhigang Wang; et al. (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Corrigendum to “MnO2 nanozyme boosts synergistic photodynamic/photothermal therapy of bacterial biofilm infections” [Chem. Eng. J. 499 (2024) 156172] - Ning Guo; Quanxin Wu; Huixuan Gan; Yan Chen; Mengnan Ran; Jia Chen; Guolie Xie; Yang Zhang; Qian Wang; Yun Liu (Chemical Engineering Journal, 2025)

Synergistic structural engineering and electronic modulation enhance upconversion emission and charge separation in LiYF4: Yb3+, Tm3+@LiYF4:Nd3+@LixTi1-xO2 core-shell nanostructure for efficient near-infrared photocatalysis - Yuxiang Xin; Jianru Wang; Ran Jia; Chaochao Dun; Zhuolei Zhang (Chemical Engineering Journal, 2025)

Postharvest fruit rot on red guava caused by Neopestalotiopsis saprophytica newly reported in Hainan Province China - Zishan Wang; Ran Zhang; Yan Xu; Changjian Zhou; Jiaxin Jin; Xue Zhao; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Crop Protection, 2024)

Comprehensive analysis of biotransformation pathways and products of chloramphenicol by Raoultella Ornithinolytica CT3: Pathway elucidation and toxicity assessment - Xueping Jiang; Hao Li; Jia Kong; Yuqi li; Xiangdong Xin; Jielin Zhou; Ran Zhang; Kwang Sik Lee; Byung Rae Jin; Zhongzheng Gui (Journal of Hazardous Materials, 2024)

MnO2 nanozyme boosts synergistic photodynamic/photothermal therapy of bacterial biofilm infections - Ning Guo; Quanxin Wu; Huixuan Gan; Yan Chen; Mengnan Ran; Jia Chen; Guolie Xie; Yang Zhang; Qian Wang; Yun Liu (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

The Diversity of Artificial Intelligence Applications in Marine Pollution: A Systematic Literature Review - Jia Ning; Shufen Pang; Zainal Arifin; Yining Zhang; U. P. K. Epa; Miaomiao Qu; Jufen Zhao; Feiyang Zhen; Abhiroop Chowdhury; Ran Guo; Yuncheng Deng; Haiwen Zhang (Journal of Marine Science and Engineering, 2024)
Marine pollution, a major disturbance to the sustainable use of oceans, is becoming more prevalent around the world. Multidimensional and sustainable ocean governance have become increasingly focused on managing, reducing, and eliminating marine pollution. Artificial intelligence has been used more and more in recent years to monitor and control marine pollution. This systematic literature review, encompassing studies from the Web of Science and Scopus databases, delineates the extensive role of artificial intelligence in marine pollution management, revealing a significant surge in research and application. This review aims to provide information and a better understanding of the application of artificial intelligence in marine pollution. In marine pollution, 57% of AI applications are used for monitoring, 24% for management, and 19% for prediction. Three areas are emphasized: (1) detecting and responding to oil pollution, (2) monitoring water quality and its practical application, and (3) monitoring and identifying plastic pollution. Each area benefits from the unique capabilities of artificial intelligence. If the scientific community continues to explore and refine these technologies, the convergence of artificial intelligence and marine pollution may yield more sophisticated solutions for environmental conservation. Although artificial intelligence offers powerful tools for the treatment of marine pollution, it does have some limitations. Future research recommendations include (1) transferring experimental outcomes to industrial applications in a broader sense; (2) highlighting the cost-effective advantages of AI in marine pollution control; and (3) promoting the use of AI in the legislation and policy-making about controlling marine pollution.

Fractionation of biomass-burning smoke-derived dissolved organic matters on the surface of clay minerals: Variations of molecular properties and components - Yinhua Zhong; Yue Cheng; Huiying Zhang; Ran Wei; Jinzhi Ni; Weifeng Chen; Hui Jia (Science of The Total Environment, 2024)

Tissue-specific responses and interactive characteristics of crop-microbe "One Health" system to soil chromium and ofloxacin pollution - Jia-Min Xu; Yaru Zhang; Kai Wang; Guodong Zhang; Ying Liu; Hao-Ran Xu; Hu-Yi Zi; Ai-Jie Wang; Yao Lv; Kun Xu; Hao-Yi Cheng (Process Safety and Environmental Protection, 2024)

Response of phosphorus fractions transformation and microbial community to carbon-to-phosphorus ratios during sludge composting - Tong Guo; Shubo Zhang; Caihong Song; Ran Zhao; Liming Jia; Zimin Wei (Journal of Environmental Management, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Improved efficiency and stability using a novel elemental sulfur-based moving-bed denitrification process - Jia-Min Xu; Hu-Yi Zi; Hao-Ran Xu; Yi-Fan Zhang; Da-Heng Ren; Ran Zeng; Gui-Jiao Zhang; Aijie Wang; Hao-Yi Cheng (Water Research, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Genomic selection for hypoxia tolerance in large yellow croaker - Jie Ding; Yibo Zhang; Xujie Li; Jiaying Wang; Xinming Gao; Qiumeng Xiang; Zhenyu Gao; Tianyi Lan; Songpeng Jia; Mengqi Lu; Ran Meng; Xuelei Wang; et al. (Aquaculture, 2024)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Two new constituents from the aerial parts of Salvia miltiorrhiza Bge - Fan Yang; Jia Li; Xin-Lei Du; Shi-Jun Wang; Xiang-Hao Xu; Yong-Qing Zhang; Ran Yang (Natural Product Research, 2023)

Platelet membrane-functionalized hollow mesoporous Prussian blue nanomedicine for comprehensive thrombolytic management by targeted enhanced fibrinolysis and ROS scavenging - Wenli Zhang; Maoyuan Sun; Yun Liu; Yu Zhang; Lian Xu; Ying Luo; Qianying Du; Jie Xu; Jia Liu; Jun Zhou; Haitao Ran; Zhigang Wang; et al. (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A relatively warm and humid Oligocene climate in the northeastern Tibetan Plateau based on a high-resolution clay mineralogical and geochemical record - Chunxia Zhang; Ran Zhang; Bin Hu; Xiaoyan Zhang; Pei Li; Ning Tan; Yunxia Jia; Zhilin He; Haibin Wu; Zhengtang Guo (Global and Planetary Change, 2023)

Emerging roles of air pollution and meteorological factors in autoimmune eye diseases - Fan Cao; Zhuo-Ran Liu; Qin-Yu Ni; Chen-Kai Zha; Shu-Jie Zhang; Jia-Min Lu; Yue-Yang Xu; Li-Ming Tao; Zheng-Xuan Jiang; Hai-Feng Pan (Environmental Research, 2023)

Fluoride resistance capacity in mammalian cells involves global gene expression changes associate with ferroptosis - Yi Zhang; Yimin Fang; Shen Zhao; Jialong Wu; Chenkang Lu; Lai Jiang; Shujun Ran; Jia Wang; Fei Sun; Bin Liu (Chemico-Biological Interactions, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Antibacterial activity and mechanism of slightly acidic electrolyzed water combined with ultraviolet light against Salmonella enteritidis - Xingyun Yuan; Yanjiao Li; Qingnan Mo; Beibei Zhang; Dengqun Shu; Lina Sun; Xianghui Zhao; Ran Zhang; Jiahui Zheng; Yingqi Jia; Yitian Zang (Food Control, 2023)

Natural restoration enhances soil multitrophic network complexity and ecosystem functions in the Loess Plateau - Jia He; Junhong Zhang; Jianyu Wang; Zhenghong Dong; Zexin Meng; Ran Xu; Yongbiao Ji; Yuyu Li; Jun Chen; Xuyang Qi; Xinsheng Wang; Xiuting Li; et al. (CATENA, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Impact of the uplift of the Central Asian Orogenic Belt and NE Tibetan Plateau on the East Asian climate since the late Miocene - Ran Zhang; Dabang Jiang; Jian Zhang; Chunxia Zhang; Yibo Yang; Yunxia Jia; Na Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The synergistic impact of SPOD and ENSO on ITCZ: observation study - Yuanhong Guan; Wen Zhou; Xiaolong Jia; Yue Zhang; Ran Dong (Climate Dynamics, 2023)

Transcriptomics analysis reveals molecular mechanism of softening and cell wall polysaccharides-disassembling in peaches treated by flow microcirculation of sodium nitroprusside medium - Yanli Zheng; Lihua Duan; Yalin Ran; Peng Zhang; Yunbin Jiang; Zhiyong Zhao; Ziqin Li; Lan Chen; Yao Tang; Xihong Li; Xiaoyu Jia (Postharvest Biology and Technology, 2023)

Response characteristics of nitrous oxide related microorganisms to biochar addition during chicken manure composting - Wenhao Zhai; Liming Jia; Ran Zhao; Xiaomeng Chen; Yunxian Zhang; Zimin Wei (Process Safety and Environmental Protection, 2023)

Hollow Co-CeO2@PEG nanospheres: Ultrasound enhanced cascade-nanozyme for synergetic anticancer - Miao Wang; Stephen Choi; Qingchen Bai; Kai Yu; Wei Guo; Feng Zhang; Ran Jia; Fengyu Qu; Huiming Lin (Chemical Engineering Journal, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Risk and protection strategies of Amolops wuyiensis intestine against gastrointestinal nematode ( Cosmocercoides wuyiensis n. sp.) infection - Yilin Shu; Yunyun Xie; Shikun Li; Liming Cai; Ying Liu; Yalin Feng; Jun He; Huijuan Zhang; Menglong Ran; Qina Jia; Hailong Wu; Linming Lu (Environmental Microbiology, 2022)
Summary Anuran amphibians are susceptible to infection by intestinal nematodes, but the damage and response mechanisms that occur in their intestines after infection are only partially understood. In this study, the intestinal disruption and response mechanisms in Amolops wuyiensis frogs infected with Cosmocercoides wuyiensis n. sp. were revealed through analysis of the intestinal histopathology, digestive enzyme activity, transcriptome and intestinal microbiota. Tissue section analysis showed histological damage and inflammation in the infected intestine, and the digestive enzyme activity indicated a decrease in digestion and absorption of some nutrients. We found that infection led to differences in the intestinal microbiota composition, including lower diversity and symbiotic relationships. The greater relative abundance of the genera Burkholderia and Rhodococcus may enhance intestinal immunity to resist pathogenic infections. A comparison of the transcriptomes of infected and uninfected intestines revealed 1055 differentially expressed genes. GO enrichment and KEGG pathways analyses suggested that the guts of infected C . wuyiensis n. sp. show enhanced complement activation, cell adhesion molecule function, NOD‐like receptor signalling pathway activity and other innate immunity responses. Among the adaptive immune responses, the intestinal immune network for IgA production was significantly enriched, and the expression of IL‐17D and transforming growth factor beta‐1 genes were upregulated in the infected intestine. These results imply that C . wuyiens is n. sp. infection of A . wuyiensis intestine may trigger innate and adaptive immune responses, which reduce the post‐infection burden. Furthermore, the intestine of A . wuyiensis may also respond to C . wuyiensis n. sp. infection by increasing metallocarboxypeptidase activity and accelerating smooth muscle contraction.

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

Neural responses to rapidly selecting color names with different novelty - Hanqing Ma; Yunyi Zhang; Jingyi Zhang; Yong Liu; Zhiliang Long; Huangyanqiu Ran; Jingwen Li; Yingmei Qin; Jia Zhao (Cognitive Neurodynamics, 2021)

Neglectella glomerata sp. nov., a new species and implications for the systematics of the genus Neglectella (Oocystaceae, Trebouxiophyceae, Chlorophyta) - Xudong Liu; Ran Zhang; Jia Feng; Fabio Rindi; Shulian Xie (Journal of Oceanology and Limnology, 2021)

Elabela prevents angiotensin II-induced apoptosis and inflammation in rat aortic adventitial fibroblasts via the activation of FGF21–ACE2 signaling - Juan-Juan Song; Mei Yang; Ying Liu; Jia-Wei Song; Xiao-Yan Liu; Ran Miao; Zhen-Zhou Zhang; Yu Liu; Yi-Fan Fan; Qian Zhang; Ying Dong; Xin-Chun Yang; et al. (Journal of Molecular Histology, 2021)

Microplastic Pollution in Nearshore Sediment from the Bohai Sea Coastline - Xiaopeng Zhu; Wen Ran; Jia Teng; Chen Zhang; Wenjing Zhang; Chaowei Hou; Jianmin Zhao; Xutong Qi; Qing Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

A Highly Selective Turn‐on Fluorescent and Naked‐eye Colourimetric Dual‐channel Probe for Cyanide Anions Detection in Water Samples - Ya Wu; Wen-Min Ding; Juan Li; Geng Guo; Shu-Zhen Zhang; Hao-Ran Jia; Yin-Xia Sun (Journal of Fluorescence, 2021)

A new anti-inflammatory lignan from Lonicerae Japonicae flos - Ran Yang; Lei Fang; Jia Li; Yong-Qing Zhang (Natural Product Research, 2021)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Morphological and Anatomical Differences among Three Seagrass Species in a High-energy Coastal Area Typically Dominated by Surfgrass in a Rocky Coastal Area of Shandong Peninsula, China - Wen-Tao Li; Jia Song; Chongfeng Zhong; Xin Hou; Ran Cheng; Pei-dong Zhang (Ocean Science Journal, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Pterostilbene, an active component of the dragon’s blood extract, acts as an antidepressant in adult rats - Liang Yang; Yuanyuan Ran; Zhenzhen Quan; Ran Wang; Qinghu Yang; Qiutian Jia; Heao Zhang; Yanhui Li; Yiheng Peng; JianHua Liang; Hui Wang; Hiroshi Nakanishi; et al. (Psychopharmacology, 2019)

A genome-wide association study on growth traits in orange-spotted grouper (Epinephelus coioides) with RAD-seq genotyping - Hui Yu; Xinxin You; Jia Li; Xinhui Zhang; Shuai Zhang; Shoujia Jiang; Xueqiang Lin; Hao-Ran Lin; Zining Meng; Qiong Shi (Science China Life Sciences, 2018)

Genetic mapping and salt tolerance of a novel D1-allelic mutant of rice (Oryza sativa L.) - Wei-jiang Tian; Xiao-qiong Zhang; Xiao-wen Wang; Jia Xie; Yang-yang Li; Ying Sun; Yi-ran Tao; Yu-zhen Xiong; Xian-chun Sang (Acta Physiologiae Plantarum, 2018)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Monazite behaviour during isothermal decompression in pelitic granulites: a case study from Dinggye, Tibetan Himalaya - Jia-Min Wang; Fu-Yuan Wu; Daniela Rubatto; Shi-Ran Liu; Jin-Jiang Zhang; Xiao-Chi Liu; Lei Yang (Contributions to Mineralogy and Petrology, 2017)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Development of a dot blot macroarray and its use in gene expression marker-assisted selection for iron deficiency tolerant apple rootstocks - Mingtao Zhu; Ran Wang; Penghao Kong; Xinzhong Zhang; Yi Wang; Ting Wu; Wensuo Jia; Zhenhai Han (Euphytica, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

SIRT1 suppresses PMA and ionomycin-induced ICAM-1 expression in endothelial cells - YuYan Jia; Peng Gao; HouZao Chen; YanZhen Wan; Ran Zhang; ZhuQin Zhang; RuiFeng Yang; Xu Wang; Jing Xu; DePei Liu (Science China Life Sciences, 2013)

Active surveillance of renal masses in von Hippel-Lindau disease: growth rates and clinical outcome over a median follow-up period of 56 months - Jin Zhang; Jia-Hua Pan; Bai-Jun Dong; Wei Xue; Dong-ming Liu; Yi-Ran Huang (Familial Cancer, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

Polymorphisms of coding region of BMPR-IB gene and their relationship with litter size in sheep - Mingxing Chu; Lihua Jia; Yingjie Zhang; Mei Jin; Hongquan Chen; Li Fang; Ran Di; Guiling Cao; Tao Feng; Qianqian Tang; Yuehui Ma; Kui Li (Molecular Biology Reports, 2011)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)